Blended learning as an effective method for school and university teachers of Kazakhstan - Ainur Kaliaskarova; Turakhan Zhundybaeva; Mochamad Bruri Triyono; Gulzhaina K. Kassymova (Jurnal Pendidikan Vokasi, 2022)
In this article, the author compares different definitions of the term blended learning given by foreign and local scientists and gives his interpretation. The article analyzes world scholars' works on blended learning, determining the advantages and disadvantages of this method. The online survey method was used to find out how far Kazakhstani teachers are familiar with the blended learning method, whether they use it or not, and understand if it is effective. The survey results showed that school and university teachers use blended learning in their lessons and will use it in the future. According to the questionnaire, the benefits of this method are that it encourages teachers to be creative, increases students' interest, and helps them to study independently. Significant shortcomings of blended learning are technical problems and poor Internet connection. Also, teachers need more time to prepare for their lessons. It is challenging for them. Although there are disadvantages to blended learning, the benefits outweigh the disadvantages. Therefore, today this method is effective.